Confucianism as the Foundation for a “Secular State”: François Bernier’s Interpretation of the Confucian Classics - Wang, Niecai (Religions, 2024)
From the late 17th to the early 18th century, Europe witnessed various intellectual debates, and it undeniably received help from places outside Europe such as China. When Chinese history, culture and thought, especially the Confucian classics translated into Latin, were introduced to Europe, they provided resources for comparison and reference for Europe’s ideological crisis. Confucius ou la Science des Princes, the Confucian classic translated by François Bernier, is a typical example. From the perspective of the cross-cultural history of ideas, after carefully analyzing the terminology used in Bernier’s translation and his understanding of Confucius’s thought, this paper will show that Bernier accepted, through the Jesuit translation, the non-religious dimension of politics and ethics in Confucianism, but unlike the Jesuits, he did not see Confucianism as needing Christianity; on the contrary, he believed that politics and ethics could be based on a purely secular philosophy. Based on his secular understanding of Confucius’s thought, Bernier reconstructed Confucius’s texts as a manual to teach European princes, regarding the prince’s virtue, reason and benevolence as the foundation of a country’s good government.